SPEKTRUM IDEOLOGIS DALAM PENAMAAN DIRI MASYARAKAT NASIONALIS - Dian Purnamasari (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to describe the ideological spectrum in the self-naming of the nationalist society with a strategic view. The method used is descriptive qualitative, with listening, note-taking, and elicitation techniques. Sources of research data are obtained from nationalist groups based on national movement organizations and nationalist party activists. The data in this study are the family names of national movement organizations and nationalist party activistsThe result of this study is that the naming of children is influenced by the ideological awareness, feeling, and memory of parents. The ideological spectrum of parents or family greatly influences the naming of themselves for their children, grandchildren, and other descendants. The majority of national groups name their children with ideological nuances with the intention of lowering the spirit, ideals, and hoping that the child will continue the ideals of his parents. It could also be that the child's fighting spirit is in line with the ideological nationalist figure who became his son's name